Respuesta :
6x^2=36x so 36x - 7x = 29x 29x + 2 = 0
29x = -2 so the answer would be -2/29
29x = -2 so the answer would be -2/29
The first step to solving this question is to write -7x as a sum
6x² - 3x - 4x + 2 = 0
Factor out 3x from the expression
3x × (2x - 1) - 4x + 2 = 0
Factor out -2 from the expression
3x × (2x - 1) - 2(2x - 1) = 0
Factor out 2x - 1 from the expression
(2x - 1) × (3x - 2) = 0
When the product of factors equals 0,, at least one factor is 0. This will make the expression look like the following:
2x - 1 = 0
3x - 2 = 0
Solve the top equation for x
x = [tex] \frac{1}{2} [/tex]
3x - 2 = 0
Solve the bottom equation for x
x = [tex] \frac{1}{2} [/tex]
[tex] \frac{2}{3} [/tex]
This tells us that the final solutions to your expression are [tex] x_{1} [/tex] = x = [tex] \frac{1}{2} [/tex], [tex] x_{2} [/tex] = [tex] \frac{2}{3} [/tex]
Let me know if you have any further questions
:)
6x² - 3x - 4x + 2 = 0
Factor out 3x from the expression
3x × (2x - 1) - 4x + 2 = 0
Factor out -2 from the expression
3x × (2x - 1) - 2(2x - 1) = 0
Factor out 2x - 1 from the expression
(2x - 1) × (3x - 2) = 0
When the product of factors equals 0,, at least one factor is 0. This will make the expression look like the following:
2x - 1 = 0
3x - 2 = 0
Solve the top equation for x
x = [tex] \frac{1}{2} [/tex]
3x - 2 = 0
Solve the bottom equation for x
x = [tex] \frac{1}{2} [/tex]
[tex] \frac{2}{3} [/tex]
This tells us that the final solutions to your expression are [tex] x_{1} [/tex] = x = [tex] \frac{1}{2} [/tex], [tex] x_{2} [/tex] = [tex] \frac{2}{3} [/tex]
Let me know if you have any further questions
:)